Artificial Intelligence and Learning Innovation: A Perception of Learning Transformation in Islamic Religious Higher Education Institutions (PTKI) - Safwandi, Ari; Mulasi, Syibran; Tassia, Fransisca; Mohd Lokman bin Marzuki; Lamkaruna, Musrijal (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2025)
This study aims to explore the perceptions of lecturers and students at Islamic Religious Higher Education Institutions (PTKI) regarding the use of artificial intelligence (AI) in learning, as well as to analyze its benefits, obstacles, ethical values, and the level of readiness for implementation. Using a descriptive quantitative approach, data were collected through a Likert-scale questionnaire distributed to lecturers and students at STAIN Teungku Dirundeng Meulaboh. The results show that lecturers' knowledge of AI has a significant relationship with the perceived benefits in learning, identified obstacles, ethical awareness, and implementation readiness. A strong correlation was found between the benefits of AI and user readiness. The study also found a significant relationship between AI use and lecturers' teaching preparedness. However, no significant relationship was found between perceived benefits and perceived obstacles. In general, respondents showed a positive attitude toward the integration of AI in learning, with the caveat that AI usage must be aligned with Islamic values. The main obstacles to AI usage were identified as limited digital infrastructure and low technological literacy, which, while present, have not completely hindered AI adoption in learning. This study emphasizes that institutional readiness and the knowledge of academic stakeholders are key to successful and contextual digital transformation in PTKI environments, particularly at STAIN Teungku Dirundeng Meulaboh.